The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/pits.20544
|View full text |Cite
|
Sign up to set email alerts
|

Reading assessment methods for middle‐school students: An investigation of reading comprehension rate and Maze accurate response rate

Abstract: This study was designed to investigate the validity of four different aloud reading comprehension assessment measures: Maze, comprehension questions, Maze accurate response rate (MARR), and reading comprehension rate (RCR). The criterion measures used in this study were the Woodcock -Johnson III Tests of Achievement (WJ-III ACH) Broad Reading Cluster Score and words correct per minute (WCPM). Pearson Product Correlations and linear regression were used to investigate possible relationships between Maze compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…These results differed slightly from the initial investigation of this newly developed measure. Although Hale et al () found MARR as having predictive capabilities, RCR emerged as a more significant predictor of reading achievement in their analyses. RCR did not significantly predict WJ III Broad Reading in any regression analyses performed as part of this study.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…These results differed slightly from the initial investigation of this newly developed measure. Although Hale et al () found MARR as having predictive capabilities, RCR emerged as a more significant predictor of reading achievement in their analyses. RCR did not significantly predict WJ III Broad Reading in any regression analyses performed as part of this study.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, further investigation of the utility of MARR as a potential measure of reading comprehension, particularly for middle and high school students, was warranted by these results. The purpose of the present study was to replicate the study by Hale et al (2011b) with a sample of upper elementary (UES) and MS students. Specifically, the potential utility of the MARR assessment method was investigated as compared to other RCBMs including WCPM, CQC, RCR, and MCR.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The National Reading Panel (RAND Reading Study Group, 2002) defined fluency in terms of accuracy, appropriate rate, and good expression. Although the definition refers to appropriate rate, rather than a fast rate per se, measures of fluency use scores such as correct words per minute in which faster is better, other things being equal (e.g., Cianco, Thompson, Schall, Skinner, & Foorman, 2015;Hale et al, 2011;McCane-Bowling, Strait, Guess, Wiedo, & Muncie, 2014;Skinner et al, 2009;Skinner, Neddenriep, Bradley-Klug, & Ziemann, 2002). As a result, we are interested in whether response rate on comprehension items answered correctly can be used to monitor progress in attaining automaticity.…”
Section: Automaticitymentioning
confidence: 99%